2019
DOI: 10.1021/acs.jpcc.9b00840
|View full text |Cite
|
Sign up to set email alerts
|

Nonclassical Adsorption of Methanol on Palladium: The Competition between Adsorption of Single Molecules and Clusters

Abstract: The adsorption of methanol on the Pd(111) surface at 80, 90, and 100 K has been studied by polarization modulation infrared reflection−absorption spectroscopy. It is found that the adsorption of methanol on the palladium surface does not proceed via the layer-by-layer mechanism. At temperatures below 100 K, methanol adsorbs molecularly to form clusters containing several hydrogen-bonded CH 3 OH molecules. These clusters have low thermal stability and decompose even at 100 K to form isolated methanol molecules … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
4
2
Order By: Relevance
“…4 In contrast to Galvez et al, 9 we observed the crystallization of these amorphous layers even at 100 K; moreover, at 120 K, methanol is completely desorbed from the palladium surface. 4 No adsorbed methanol species were observed at 130 K. This means that there is a size effect in the condensation and crystallization of small molecules at cryogenic temperatures, and the physical properties at least of bulk 1 Boreskov Institute of Catalysis SB RAS, Novosibirsk, Russian Federation solid methanol and a thin layer of condensed methanol differ. To elucidate this effect, we examined the multilayer adsorption of methanol and ethanol on the Pt (111) surface in a temperature range between 80 and 130 K. These molecules are of different lengths, which can affect the crystallization process.…”
Section: Introductioncontrasting
confidence: 83%
See 2 more Smart Citations
“…4 In contrast to Galvez et al, 9 we observed the crystallization of these amorphous layers even at 100 K; moreover, at 120 K, methanol is completely desorbed from the palladium surface. 4 No adsorbed methanol species were observed at 130 K. This means that there is a size effect in the condensation and crystallization of small molecules at cryogenic temperatures, and the physical properties at least of bulk 1 Boreskov Institute of Catalysis SB RAS, Novosibirsk, Russian Federation solid methanol and a thin layer of condensed methanol differ. To elucidate this effect, we examined the multilayer adsorption of methanol and ethanol on the Pt (111) surface in a temperature range between 80 and 130 K. These molecules are of different lengths, which can affect the crystallization process.…”
Section: Introductioncontrasting
confidence: 83%
“…Recently, we have studied the multilayer adsorption of methanol on palladium and found that condensation of methanol leads to the formation of an amorphous phase at 90 K only. 4 In contrast to Galvez et al, 9 we observed the crystallization of these amorphous layers even at 100 K; moreover, at 120 K, methanol is completely desorbed from the palladium surface. 4 No adsorbed methanol species were observed at 130 K. This means that there is a size effect in the condensation and crystallization of small molecules at cryogenic temperatures, and the physical properties at least of bulk 1 Boreskov Institute of Catalysis SB RAS, Novosibirsk, Russian Federation solid methanol and a thin layer of condensed methanol differ.…”
Section: Introductioncontrasting
confidence: 83%
See 1 more Smart Citation
“…Moreover, no bands in the range of 3200− 3350 cm −1 , which are typical of the ν(OH) stretching vibrations of adsorbed molecules of methanol, are observed. 19 This means that even at 150 °C, methanol is dissociatively adsorbed on vanadia, forming methoxy groups.…”
Section: Resultsmentioning
confidence: 99%
“…The temperature was measured using a K-type thermocouple spot-welded to the back of the plate. The sample holder could be transferred between the analytical chamber and the HPC using a manipulator . Methanol and oxygen were introduced into the HPC separately by using variable leak valves.…”
Section: Methodsmentioning
confidence: 99%